Macro And Micro Nutrients in The Soil of The Mangrove Forest Area, Bunaken Marine Park - Anwar, Chairil; Wonggo, Djuhria; Mongi, Eunike; Dotulong, Verly (Sam Ratulangi University, 2025)
The purpose of this study is to determine the pH level and macro and micronutrient content in the soil of the mangrove forest area in Bunaken Marine Park, Meras Village, Wori District, North Sulawesi Province. Soil samples were collected from both dry soil and waterlogged soil. The samples were then taken to the laboratory for analysis of macro- and micronutrients as well as pH levels. The analysis used includes: Nitrogen (N) analysis following SNI 7763:2018, section 6.6.1; Phosphorus (P) analysis following SNI 7763:2018, section 6.7; Elements K, Ca, Fe, Mg, Cu, Zn, B, Mn, and Mo analyzed using IK-1.13 Method for Determination of Metal Minerals in Food and pH analysis using SNI 01-2891-1992. The research results show that the pH values of dry and waterlogged soil are 6.67 and 6.0, respectively, which are considered good categories. The macro-nutrient analysis results for N, P, K, and Mg are classified as good because they exceed the minimum requirements set by SNI 7763:2024. However, the Ca element is classified as not good as it exceeds the maximum limit specified by SNI 7763:2024. For micro-nutrients, Fe (Iron) content is 13,682 ppm, which falls under the good category since it is below the maximum limit of 15,000 ppm as per SNI 7763:2024. Zn (Zinc) content is 0.4807 ppm, which is also considered good, as it does not exceed the maximum limit of 5,000 ppm as per SNI 7763:2024. Keywords: Meras Mangrove Forest, Nutrients, pH. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui kandungan pH, unsur hara makro dan mikro pada tanah kawasan hutan mangrove taman laut Bunaken desa Meras kecamatan wori propinsi sulawesi utara. Pengambilan sampel tanah diambil pada tanah yang kering dan tanah yang tergenang air. Sampel tanah dibawa ke laboratorium untuk dianalisa unsur hara makro, mikro dan pH. analisa yang digunakan adalah Analisa N dengan SNI 7763:2018 butir 6.6.1. Analisa P dengan SNI 7763:2018 Butir 6.7. unsur K, Ca Fe dan Mg, Cu, Zn, B, Mn dan Mo dengan metode IK-1.13 Penentuan Mineral Logam pada Pangan dan Non Pangan. Dan pH dengan metode SNI 01-2891-1992. Hasil penelitian bahwa nilai pH tanah kering dan tergenang adalah pH 6,67 dan 6,0. Termasuk kategori baik. Hasil Analisa unsur makro yaitu N, P, K dan Mg adalah adalah katgori baik karena melebihi syarat minimum dari SNI 7763:2024, sedangkan nilai Ca kategori tidak baik karena melebihi batas maksimum SNI 7763:2024. Unsur mikro Fe adalah 13682 ppm termasuk kategori baik karena mempunyai nilai lebih rendah dari 15.000 ppm sebagai batas maksimum dari SNI 7763:2024. Unsur Zn adalah 0.4807 ppm termasuk kategori baik karena tidak melebihi batas maksimum 5.000 ppm sebagai batas maksimum dari SNI 7763:2024. Kata kunci: Hutan Mangrove Meras, unsur hara, pH